Obstacle Avoidance Path Planning for Double Manipulator based on Improved Artificial Potential Field Method - Xue Yang; Yu Zhicheng; Wu Haidong; Zhang Ning; Sun Yue (Jixie chuandong)
An obstacle avoidance path planning algorithm based on improved artificial potential field method is proposed for dual 6-DOF manipulator. Firstly，the cooperative working space of double manipulator is analyzed，and the possibility of self-collision is confirmed. Secondly，obstacle avoidance motion planning is carried out for the main arm against static obstacles，and path planning for the main arm is completed. Then，the main arm is taken as the dynamic obstacle when the slave arm moves，and obstacle avoidance motion path is planned for the slave arm. The new potential energy function is used to replace the potential energy function of the traditional artificial potential field method to carry out obstacle avoidance path planning for the double manipulator. Since the traditional artificial potential field method is easy to fall into the defect of local minimum value in the obstacle avoidance path planning of the manipulator，the virtual attraction point is added to avoid this situation. Simulation results show that this method is easily realized and can meet the requirements of double manipulator obstacle avoidance. It can effectively plan a collision-free path for the dual 6-DOF manipulator.